Conjoint adolescent developmental trajectories of alcohol and marijuana use and early adult outcomes among North American Indigenous people. (March 2021) - Sittner, Kelley J.; Hautala, Dane S.; Walls, Melissa L.
Highlights: We analyzed dual trajectories of Indigenous adolescent marijuana and alcohol use. Four groups emerged: non-use (34%); alcohol only (14%); and two co-use groups. Early marijuana use was linked to early alcohol use. Infrequent alcohol use was linked to abstaining from marijuana use. Co-users of alcohol and marijuana in adolescence had poorer outcomes in adulthood. Abstract: Objective: The current study examined the developmental interrelationships between alcohol and marijuana use trajectories from ages 10 to 18 years in a sample of North American Indigenous adolescents. Distinct co-use groups were formed to create profiles of young adult outcomes. Method: Dual group-based trajectory models of marijuana and alcohol frequency were estimated using data from a longitudinal community-based participatory study of Indigenous adolescents from the upper Midwest and Canada. Joint probabilities were used to create co-use groups, and profiles were created using early adult (Mean Age – 26.28 years) outcomes. Results: Four joint trajectory groups were identified: 1) no marijuana and no/low alcohol use (34.4%), 2) mid-onset alcohol only (14%), 3) mid-onset co-use starting at age 13 (24%), and 4) early-onset co-use starting at age 11 (22%). High probabilities existed that adolescents would use marijuana early if they began drinking alcohol at the youngest ages, and that adolescents would not use marijuana if they drank infrequently or delayed drinking until mid-adolescence. Adult outcomes were poorer for the early- and mid-onset co-use groups, but there were few differences between the no/low use and alcohol-only groups. Conclusion: Co-use of marijuana and alcohol was associated with poorer outcomes in early adulthood, particularly for the group with an earlier age of onset. Abstaining from either substance in adolescence was associated with better outcomes.